2016
DOI: 10.1111/ene.12976
|View full text |Cite
|
Sign up to set email alerts
|

Brain derived neurotrophic factor in multiple sclerosis: effect of 24 weeks endurance and resistance training

Abstract: In conclusion, BDNF concentration of persons with RRMS was lower compared to HCs and increased after 24 weeks of exercise in persons with MS, compared to the non-exercise MS control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 33 publications
(67 reference statements)
7
87
2
14
Order By: Relevance
“…periods of low-to-moderate neuronal activity, which may partly explain the findings of these metaanalyses. Reporting some of the most clear study findings on chronic circulating (serum) BDNF levels in pwMS, Wens and colleagues showed that 24 weeks (60 planned sessions) of combined RT and aerobic training elicited significant between-group increments (Wens et al, 2016). The discrepancy between our findings of their study, may therefore be explained by a smaller total training volume in the present study (48 planned sessions) and/or the absence of aerobic training.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…periods of low-to-moderate neuronal activity, which may partly explain the findings of these metaanalyses. Reporting some of the most clear study findings on chronic circulating (serum) BDNF levels in pwMS, Wens and colleagues showed that 24 weeks (60 planned sessions) of combined RT and aerobic training elicited significant between-group increments (Wens et al, 2016). The discrepancy between our findings of their study, may therefore be explained by a smaller total training volume in the present study (48 planned sessions) and/or the absence of aerobic training.…”
Section: Discussioncontrasting
confidence: 67%
“…which hereafter returns to baseline (Bansi et al, 2013;Briken et al, 2016;Castellano and White, 2008;Gold et al, 2003), along with chronic increases after 3-24 weeks of aerobic training alone (Bansi et al, 2013;Castellano and White, 2008) or in combination with pilates training (Ozkul et al, 2018) or RT (Wens et al, 2016). However, in line with the negative findings of the present RT study, a number of aerobic training studies have also failed to observe acute (Bansi et al, 2013;Schulz et al, 2004) and chronic (3-9 weeks) increases in circulating BDNF levels (Briken et al, 2016;Schulz et al, 2004;Zimmer et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Also noteworthy is a review by Tomlinson, Leiton, and Colognato (2016) in which the authors document how physical activity, environmental enrichment, and motor experiences promote more effi cient neuronal myelinization and, conversely, that social retreat, inadequate physical activity, and poor environmental experiences reduce it. Wens et al (2016) report an increase in BDNF in subjects with multiple sclerosis as a result of aerobic activity over the course of six months. Have et al (2016) wanted to test the eff ects o f motor activity on creative performance, as well as executive and math functions in primary school children, and correlate it with their body mass index.…”
Section: Physical Activity and Cognitive Processes: What Changes In "mentioning
confidence: 94%